Cocoa pests and diseases - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Cocoa pest and disease management in Southeast Asia and Australasia FAO plant production and protection paper 112 edited by P J Keane and C A J Putter 1992 223pp ISBN 92 5 103039 1 Pbk Distribution and Sales Section FAO Via delle Terme di Caraca